Significance of riparian forests for the conservation of Central African primates - (:unkn) unknown (My University, 2005)
We compared the structure of 12 Central African primate communities, 6 in riparian forests and 6 in adjacent terra firma forests and discussed the implications for primate conservation. The communities in riparian forests included on average 1.5 times more primate species than those in terra firma forests due to the fact that riparian forests shelter 4 specialist species and 6-7 generalist species. The results differ from findings in Amazonia where riparian forests consistently have fewer primate species than terra firma forests accommodate. This may be partly explained by the water level amplitude in Amazonian riparian forests, which deterred the radiation of semiterrestrial species. In Africa, most riparian-specialist primates are terrestrially-adapted and have access to an enlarged food niche. In terms of African primate conservation, we recommend protecting riparian forests and adjacent terra firma forests so that most of the lowland forest diversity is captured. The linear shape of riparian forests (which allows gene flow over long distance) and their persistence in anthropic landscape (because they represent lands of lesser value for agriculture and logging than mainland forests) predispose them to act as biodiversity sanctuaries.
Keywords: African Research